PENYULUHAN KESEHATAN: BAHAYA ROKOK BAGI KESEHATAN DI PONDOK PESANTREN AN NAHDLAH MAKASSAR - St. Maryam; Rahmawati; Emelda, Andi; Razak, Rais; Santi, Irma; Amriati, Rezki (Akademi Farmasi Yamasi Makassar, 2024)
Smoking is one of the main risk factors for several chronic diseases that can result in death, so it can be a big problem for public health. Educational activities about the dangers of smoking for health were given to Aliyah students at the An-Nahdlah Islamic Boarding School in Makassar with a total of 40 participants. The aim of this activity is to increase students' awareness of the bad effects of smoking on health. This activity method begins with filling out a pre-test knowledge questionnaire about the dangers of smoking, which is then continued with counseling by the resource person and completing the post-test questionnaire again. The results of filling out the questionnaire after the counseling had increased, namely 90% of students understood the bad effects of smoking. During the counseling, students were very enthusiastic in listening to the presenters, so it is hoped that this activity will be encouraged, especially in the world of education.